Therapeutic roles and molecular mechanisms of Cuscutae Semen in reproductive diseases - Li, Kun; Zheng, Haixia; Hao, Wenjie; Kong, Yanni; Zhou, Qianru (Frontiers in Immunology, 2025)
Cuscutae Semen (CS), one of the herbs in traditional Chinese medicine, has been recorded for a long time and contains various bioactive compounds, including flavonoids, phenolic acids, lignans, and polysaccharides. These compounds contribute to the medicinal effects on reproductive health. This review examines the therapeutic applications of CS in male and female reproductive diseases, its toxicity, and potential herb-drug interactions. This study focused on the medicinal roles and possible molecular mechanisms of CS in the treatment of reproductive diseases, such as male and female infertility, premature ovarian insufficiency, recurrent spontaneous abortion, and polycystic ovary syndrome. This review examines the mechanisms by which CS regulates the hypothalamic-pituitary-gonadal axis, hormone levels, and key molecules and signaling pathways crucial for reproductive health. By elucidating the potential mechanisms of CS action in reproductive endocrine disorders, this study aimed to provide a scientific basis and evidence for its clinical application in these conditions. These findings provide insights into the molecular mechanisms by which CS has significant potential for treating a range of reproductive disorders.